Dimensi Nilai Budaya Terhadap Kualitas Kinerja Dosen - Shella Budiawan (Jurnal Manajemen Bisnis, 2020)
The qualified lecturers have good abilities in accordance with their respective fields (competent), motivation, innovative, high work discipline and support by reliable management, physical environment and good organizational culture. Cultural values of good performance supported the creation of good quality performance. Supported by the achievement of Innovation, Detail, Focus on Results, Focus on Team, Aggressiveness, and Stability that must be possessed by lecturers to create quality performance. This research uses a quantitative design with a causal and interactive suppressor between Cultural Values of Performance (X) and the Quality of Lecturer Performance (Y). The results of this reseach prove the existence of a causal and interactive relationship between these two variables, which is expressed through the results of data analysis using the SPSS 23 analysis program to determine between the culture value of performance and the quality of lecturer performance.